If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5a-6=2(a-1)+11a+1
We simplify the equation to the form, which is simple to understand
5a-6=2(a-1)+11a+1
Reorder the terms in parentheses
5a-6=+(+2a-2)+11a+1
Remove unnecessary parentheses
+5a-6=+2a-2+11a+1
We move all terms containing a to the left and all other terms to the right.
+5a-2a-11a=-2+1+6
We simplify left and right side of the equation.
-8a=+5
We divide both sides of the equation by -8 to get a.
a=-0.625
| x^2-75x=0 | | 2x+3x^2=4x-5x^2 | | x+y=3600 | | 2b+3+4b+5-6a= | | 5x(x+2)=60 | | x(3x-2y)-5x^2=12 | | x(3x-3y)-5x^2=12 | | 7x^2-3x=4x | | 3x(x-4)= | | 9-8x=91-22x | | 4y+3w= | | 8x-6w= | | 81a^2-8=0 | | X^2+3x-22.5=0 | | X^2+3x-225=0 | | X^2+3x+225=0 | | 16y^2-25-(-4y+5)(8y+15)=0 | | x^4+6x^3+8x^2-4x-4=0 | | (c-7)(c+7)=0 | | c^2+49=0 | | 2x+35=24 | | (4v)=12 | | (10x)=30 | | 5y+4x+10=11x+30 | | 11x=-30 | | (4x-1)(4x+8)= | | 6y=7y-y | | 0.5x=4.7x+8 | | 589x=25425 | | 7+5(s-3t)= | | 0=-5x^2-150x | | 2r-(5-r)=-3(2a-1) |